Tổng hợp vật liệu mao quản trung bình MCM-41 biến tính làm xúc tác cho phản ứng chuyển hóa benzyl ancol - Đức, Trương Đình; Thu, Hoa Hữu; Bằng, Nguyễn Văn (Vietnam Journal of Chemistry, 2012)
MCM-41 (Mobil Composition of Matter No. 41) is one of the most popular mesoporous molecular sieves that were first synthesized by Mobil’s researchers in 1992. This material also possesses large surface area, which can up to more than 1000 m2g-1. Furthermore, the pore diameter of this material can be easily controlled within mesoporous range between 1.6 to 10 nm by adjusting the synthesis conditions and/or by employing surfactants with different chain lengths in the preparation. Mesoporous material MCM-41 (p6mm) has been synthesized using a commercially available template cetyl trimethyl ammonium bromide (CTAB) in aqueous solution. Transitional metal oxides (TiO2) supported on mesoporous materials (MCM-41) has redox properties such as x%TiO2/MCM-41 catalysts (x = 1; 3 and 5% in weight). The above catalysts were characterized by XRD, TG-DTA, TEM, BET and showed that obtained samples with surface area of 1009 m2g-1, pore size diameter of 3.5 nm and highly ordered structure. The structures of mesoporous material supported metal oxides were not changed. Catalytic activities of these materials were evaluated by the oxygenation reaction of benzylancohol. The results obtained showed that catalytic activity of 3%TiO2/MCM-41 was highest with conversion up to 55.24% and selectivity of 37.28%.